Population ageing and its effects on the German economy - Dirk Ulbricht; Dmitry Chervyakov (Deutsches Institut für Wirtschaftsforschung (DIW), 2015)
The latest long-term projection of Germany's population implies a clear trend: even though slight growth is expected over the next decade, a decline in the future is almost inevitable. Furthermore, an ageing society combined with a low fertility rate will lead to massive shrinkage of the working-age population. What are the social and economic consequences of these developments? Is a decline in economic growth unavoidable? We present the results of the long-term population projection and summarize the various effects population ageing may have on Germany.
Keywords: 330